An early experience on the effect of solid organ transplant status on hospitalized COVID‐19 patients. Issue 7 (13th January 2021) - Nair, Vinay; Jandovitz, Nicholas; Hirsch, Jamie S.; Abate, Mersema; Satapathy, Sanjaya K.; Roth, Nitzan; Miyara, Santiago J.; Guevara, Sara; Kressel, Adam M.; Xiang, Alec; Wu, Grace; Butensky, Samuel D.; et al.
Abstract : We compared the outcome of COVID‐19 in immunosuppressed solid organ transplant (SOT) patients to a transplant naïve population. In total, 10 356 adult hospital admissions for COVID‐19 from March 1, 2020 to April 27, 2020 were analyzed. Data were collected on demographics, baseline clinical conditions, medications, immunosuppression, and COVID‐19 course. Primary outcome was combined death or mechanical ventilation. We assessed the association between primary outcome and prognostic variables using bivariate and multivariate regression models. We also compared the primary endpoint in SOT patients to an age, gender, and comorbidity‐matched control group. Bivariate analysis found transplant status, age, gender, race/ethnicity, body mass index, diabetes, hypertension, cardiovascular disease, COPD, and GFR <60 mL/min/1.73 m 2 to be significant predictors of combined death or mechanical ventilation. After multivariate logistic regression analysis, SOT status had a trend toward significance (odds ratio [OR] 1.29; 95% CI 0.99–1.69, p = .06). Compared to an age, gender, and comorbidity‐matched control group, SOT patients had a higher combined risk of death or mechanical ventilation (OR 1.34; 95% CI 1.03–1.74, p = .027). Abstract : In an early experience from New York, hospitalized solid organ transplant recipients with COVID‐19 are more likely to reach a combined endpoint of death or mechanical ventilation than a large population of comorbidity‐matched controls.